OP0182 SYNTHETIC PEPTIDES TARGETING CD206 INHIBIT PATHOGENIC MACROPHAGES IN SYSTEMIC SCLEROSIS. (June 2019) - Lopez, Henry; Kumar, Kimti; Martin, George; Jaynes, Jesse; Stanway, James; Abdi, Bahja Ahmed; Arumalla, Nikita; Karrar, Sarah; Morris, Sian; Denton, Christopher; Abraham, David; Shiwen, Xu; et al.
Abstract : Background: In systemic sclerosis, activated macrophages having M2-like properties are believed to contribute to the fibrotic pathology by secreting profibrotic factors such as TGFβ. Certain synthetic peptides (10-12mers) studied here coopt the mechanism used by macrophages to detect bacteria by binding to certain regions of CD206, a receptor highly expressed in the M2 macrophages, and repolarise them to an M1 phenotype. Objectives: We aimed to determine the macrophage activation signature in SSc, assess CD206 as a biomarker of ongoing fibrotic activity, and measure the effect of the peptides on macrophage activation and macrophage-fibroblast cross-talk. Methods: sCD206 was assayed in plasma (n=50 healthy, 50 limited SSc, 50 diffuse SSc), and suction blister fluid (BF) obtained over active lesions by ELISA. sSIGLEC (monocyte interferon signature) and IL-31 (Th2 signature) were assayed for comparison. Cell surface CD206 and DAMP receptor P2X7, were assayed by flow cytometry. The macrophage activation signature was investigated further by qPCR for inflammatory M1, as well as M2-like gene expression ( IFNγ, Arg1, CD2106 ). Macrophage-fibroblast cross talk was assessed using media transfer following heat activation to SSc dermal fibroblasts assayed by qPCR for collagen I. The macrophage secretome was determined by Luminex and ELISA. Results: CD206 was significantly elevated in SSc BF (SSc median sCD206 42, HC 31 pg/ml, p<0.041). Plasma sCD206 was raised in diffuse versus limited SSc (P<0.0103) and was correlated with ESR (R=0.364, p<0.009) and sSIGLEC (R=0.244, p<0.05), but not disease duration or IL-31. By flow cytometry both CD206 and P2X7 were highly expressed by SSc macrophages (mean fluorescence SSc, 776.1 SD=409.1, 724.4 SD=455.3 vs HC 632.2 SD=73.7, 472.9 SD=25.4), correlating with modified Rodnan Skin Score (mRSS) (p<0.05, r=0.51). Double positive P2X7 and CD206 cells were seen in a subgroup with higher mRSS. Four RP peptides (RP182, 185, 832 & 837) were assessed for effect on growth of SSc and control macrophages. In general, the RP peptides selectively inhibited SSc macrophage growth, with RP185 and RP832 reaching significance (p<0.05) for 1 and 10µM concentrations at 96 hours. Pro-fibrotic cross-talk leading to elevated fibroblast collagen I, was characteristic of 4 out of 9 SSc macrophage cell lines examined. A mixed activation signature was identified by qPCR of the fibroblast-stimulating macrophages (elevated Arginase1, CD206 and IFNγ) but not the non-fibroblast inducing cell lines. Pre-treatment of the pro-fibrotic SSc macrophages with RP832, but not the others, eliminated the pro-fibrotic cross-talk (fibroblasts treated with SSc macrophage media mean collagen I, 1995 (SEM 149), RP832 treated macrophages 1551 (SEM 133) p<0.038 relative expression units, paired t test), and suppressed the macrophage activation signature (reduced mean Arg1 p<0.030, CD206 p<0.058, IFNγ p=0.058, paired t test). Secretome analysis confirmed the mixed activation signature of SSc macrophages including elevated total TGFβ, PDGF-BB, sCD40L as well as inflammatory factors IL-6, IL-1β, TNFα and type I cytokine IFNγ. Treatment with RP 832c reduced TGFβ in 6 out of 9 SSc macrophage cell lines but this did not reach statistical significance. Conclusion: A macrophage activation signature is identified in SSc patients, in proportion to the severity of disease. A mixed activation signature with inflammatory as well as pro-fibrotic M2-like properties is seen. RP peptides, which target the cells via CD206, reduce the activation signature and inhibit pro-fibrotic cross talk in these cells. Disclosure of Interests: : Henry Lopez Shareholder of: Murigenics, Riptide Bioscience, Employee of: Pfizer, Kimti Kumar: None declared, George Martin Shareholder of: Riptide Bioscience, Jesse Jaynes Shareholder of: Riptide Bioscience, James Stanway: None declared, Bahja Ahmed Abdi: None declared, Nikita Arumalla: None declared, Sarah Karrar: None declared, Sian Morris: None declared, Christopher Denton Grant/research support from: GlaxoSmithKline, Inventiva, CSF Behring, Consultant for: Roche-Genentech, Actelion, GlaxoSmithKline, Sanofi Aventis, Inventiva, CSL Behring, Boehringer Ingelheim, Bayer, David Abraham: None declared, Xu Shiwen: None declared, Richard Stratton: None declared